Imagens ressecadas: a representação iconográfica do nordeste nos livros didáticos de história - Silva, Enock Douglas Roberto da (2019)
This dissertation seeks to investigate how the Northeast region is represented in the didactic books provided by the PNLD, reflecting on certain ideas that started to be linked to this region of the country. To do so, we used four collections of textbooks of History from the 4th to the 9th grade of elementary school, through the analysis of images and speeches, as well as the study and historical retrospective pertinent to the theme. The specific objectives of the research seek to verify regional discourses about the Northeast (re) elaborated scientifically, identifying reproductions of stereotypes, highlighting the possible implications in the construction of an image of the region; to reflect on the didactic book and images as mechanisms of production and reproduction of representations, and to analyze the curricular guidelines on the regional contents of the Northeast region with a focus on the observation of the rupture and / or reproduction of paradigms. Methodologically, the research is qualitative, bibliographical and documentary. Using as theoretical reference the studies of Gil (2008), Minayo (2001) and Fonseca (2011). In the field of image analysis the reasoning was made in light of the concepts of Joly (2007), Mauad (2000) and Neiva (1993). As for the concept of representation, we are based on Chartier (1990, 1991) and Certeau (1994), making possible to think the image symbolically, of the context of production and its intentionalities. Burke (2004), Pesavento (2005) and Mauad (2004) were referenced in the aspect of historical and symbolic understanding of images. About the textbook we refer to Bittencourt (1993) and Schmidt (2006). On the Northeast and its arrays of thought in Albuquerque Jr (2001, 2007), Freyre (2010), Guerra (1981) and Furtado (1997). Therefore, the research presents reflections about the teaching of History and some elements of its constitution, such as the didactic book, images and discourses that we (re) produce daily in the classroom, often loaded with prejudiced elements not perceptible by common sense